The efficacy of cryolipolysis treatment on arms and inner thighs - Rungsima Wanitphakdeedecha (2018)
© 2015, The Author(s). Cryolipolysis has emerged as a new non-invasive body contouring method using controlled cooling to selectively destroy fat cells. Previous studies demonstrated the safety and efficacy of cryolipolysis for the reduction of localized subcutaneous fat on abdomen and flanks. Recently, the new flat cup vacuum applicator has been developed to treat localized subcutaneous fat on arms and inner thighs. The objective of this study was to determine the efficacy of non-invasive cryolipolysis for body contouring with a flat cup vacuum applicator on arms and inner thighs. Twenty females with excess localized subcutaneous fat on arms or inner thighs received a single cryolipolysis treatment. Forty treatment areas have been treated including 10 arms and 30 inner thighs. Subjects were evaluated using standardized photographs and measurements of body weight and circumference of arms or inner thighs at baseline, 3-month, and 6-month follow-up visits. Physicians’ evaluation and patient’s satisfaction of clinical improvement were also measured. Of all 20 subjects, 17 (10 arms and 24 inner thighs) completed the treatment protocol and attended all follow-up visits. Three subjects were withdrawn from the study, 1 subject could not complete the treatment session due to pain and numbness during treatment, 1 subject became pregnant after treatment, and the other subject could not attend all required follow-up visits. There was significant circumference reduction of 0.41 and 0.72 cm at 3-month and 6-month follow-up visits (p = 0.017), respectively. Most of the patients were rated to have 1–25 % improvement at 6 months after treatment and were satisfied with the treatment outcome. The new cryolipolysis flat cup vacuum applicator provided beneficial effects for circumferential reduction of arms and inner thighs.